SUFFIXAL UNIVERBIZATION IN THE HUTSUL SUBDIALECT - Dumchak , I. M. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
In the article univerbization is analyzed as a phenomenon of the secondary nomination. A precondition for active use of suffixal univerbs in the spoken dialect language is speakers’ attempts to make a statement more expressive, give emotionality and naturalness to it. The appearance of univerbs is also the result of economy of linguistic efforts and resources. The object of the research is a dictionary "Hutsul dialect. Concise Dictionary" (ed. J. Zakrevska). The aim of the article is to clarify the structural types of derivatives-univerbs, describe their lexical-semantic groups. The term "univerbization" in contemporary linguistics is interpreted variously: as a word-forming and stylistic phenomenon of the secondary nomination; as a phenomenon of primary nomination when creating any derivative is associated with the recovery of a semantic word-forming paraphrase; just as a "kind of a method of suffixal word formation, in which the phrase by means of suffixation is en rolled into a word. Univerbization is supposed to be a word-forming act in the result of which a multiword lexical unit (as a usual it is a persistent phrase) is transformed into a one-word equivalent – univerb. The structure of the parasynthetic notions and derived univerbs is determined, productive suffixes are distinguished. The most useful lexicalsemantic groups of univerbs of Hutsul subdialect are determined as well. Our patterns of univerbs have indicated foods, names of plants and their processed products, locative names, names of vessels and repositories for anything and others.